Consumer Perception of Charolais Mixed Breed (Lembu Sado) Meat Consumption in Terengganu, Malaysia - Hisham, Ain Dania Badrul; Suhaimi, Nurul Aisyah Mohd; Arumugam, Nalini; Nor, Norhariani Mohd; Indrawan, Dikky (Jurnal Manajemen & Agribisnis, 2022)
Charolais mixed breed, also known as Lembu Sado locally, is a quite new cattle breed in Malaysia. Lembu Sado usually been raised in certain states in Malaysia such as Terengganu, Kelantan, Pahang, and Johor. Consumer perceptions on Lembu Sado meat for consumption are being measures since Lembu sado meat become relevant as one of meat beef. This study aims to identify the level of consumer perception on Lembu Sado meat consumption and to determine the significant factor of consumer perception that influence Lembu Sado meat consumption. A Google form survey was distributed to 50 respondents across Terengganu, to test the hypotheses whether the perception factors such as psychological, sensory, and marketing factors had influenced consumer consumption of Lembu Sado meat. Descriptive analysis and factor analysis were employed in this study. The results indicated that leanness of meat, health, ethnicity and advertisement are the main factors that influence the consumption of Lembu Sado meat. The findings may help consumer to decide which variables they should consider when purchasing Lembu Sado meat and also give them a clear view on what to expect when consuming Lembu Sado meat in the future. Keywords: consumer perception, lembu sado, factor analysis, Terengganu